The pricing of sovereign risk and contagion during the European sovereign debt crisis - John Beirne; Marcel Fratzscher (European Central Bank (ECB), 2013)
The paper analyses the drivers of sovereign risk for 31 advanced and emerging economies during the European sovereign debt crisis. It shows that a deterioration in countries' fundamentals and fundamentals contagion – a sharp rise in the sensitivity of financial markets to fundamentals – are the main explanations for the rise in sovereign yield spreads and CDS spreads during the crisis, not only for euro area countries but globally. By contrast, regional spill overs and contagion have been less important, including for euro area countries. The paper also finds evidence for herding contagion – sharp, simultaneous increases in sovereign yields across countries – but this contagion has been concentrated in time and among a few markets. Finally, empirical models with economic fundamentals generally do a poor job in explaining sovereign risk in the pre-crisis period for European economies, suggesting that the market pricing of sovereign risk may not have been fully reflecting fundamentals prior to the crisis.
Keywords: E44; F30; G15; C23; H63; 330; bond spreads; CDS spreads; contagion; ratings; sovereign debt crisis; sovereign risk